2018
DOI: 10.21608/ejss.2018.5594.1213
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Evaluation of Some Soils Representing the Geomrphic Units in the Northwestern Coast of Egypt.

Abstract: Supplement USDA (2014) the 7 th. Approximation and its modification into the two orders; Entisols and Aridisols, of which soils related to the order Aridisols, are the more concerned herein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Calcium carbonate content ranges between 20.45 to 81.82 %. Also, Bahnasawy (2018) showed that soil texture of the studied profiles ranges between loamy sand and light clay except the subsurface layer of profile 3 in the soils of Marsa Matruh which is sandy texture. Organic matter (OM) content is quite low being in the range of 0.2 to 1.4 g/100g.…”
Section: Some Physical and Chemical Properties Of The Study Soilmentioning
confidence: 85%
“…Calcium carbonate content ranges between 20.45 to 81.82 %. Also, Bahnasawy (2018) showed that soil texture of the studied profiles ranges between loamy sand and light clay except the subsurface layer of profile 3 in the soils of Marsa Matruh which is sandy texture. Organic matter (OM) content is quite low being in the range of 0.2 to 1.4 g/100g.…”
Section: Some Physical and Chemical Properties Of The Study Soilmentioning
confidence: 85%
“…Results in Table 3 showed that the clay minerals in studied soils were mainly quartz and kaolinite (from level common to dominant) with variable quantities of other minerals. Bahnasawy(2018)found the dominance of quartz in the northwest coast soils. Although smectite mineral was present in moderate amounts of soil profiles No.…”
Section: Semi-quantitative Clay Mineral Of the Clay Fractionsmentioning
confidence: 99%
“…8 at a depth of 0-50 cm with an average value of 30.57%. Bahnasawy, (2018) and Ali et al, (2018)found that kaolinite is the dominant mineral compared to other clay minerals. These results showed that the soil under study was not exposed to severe weathering.…”
Section: Mineral Compositions Of Clay Fractionsmentioning
confidence: 99%
“…Distributions of the resistant minerals indicate that the soils are generally of multi-origin and/or multi-depositional regime and are thus young. X-ray diffraction of clay minerals showed the predominance of kaolinite, followed by montmorillonite (Bahnasawy, 2018). Ismail, et al (2012) studied the mineralogy of the sand fraction in south east of El-Qattara Depression (near the studied area).…”
Section: Introductionmentioning
confidence: 99%